EFFECT OF SEED STIMULATION BY ALPHA-AMYLASE ENZYME, STIMULUS TEMPERATURE DEGREE AND SOWING DATES ON SOME YIELD CHARACTERISTICS OF SORGHUM: EFFECT OF SEED STIMULATION BY ALPHA-AMYLASE ENZYME, STIMULUS TEMPERATURE DEGREE AND SOWING DATES ON SOME YIELD CHARACTERISTICS OF SORGHUM (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted at Research Station A, Department of Field Crops, College of Agricultural Engineering Sciences - University of Baghdad, in Al-Jadriya for the fall season of 2023. The study aimed to investigate the impact of seed priming with alpha-amylase enzyme and induced temperature on yield traits of sorghum. A randomized completely block design (RCBD) with split plot arrangement with three replications and two factors was employed. The first factor included planting dates (June 25, July 15, and August 5) denoted as D1, D2, and D3, respectively, in sequence. The second factor included enzyme priming treatments (0.5, 1, and 1.5 mg L-1) denoted as T1, T2, and T3, respectively, in sequence, along with a control treatment (distilled water) denoted as T0. The results showed that the plants grown in the second date (D2) had the highest rate of number of grains per head (5345 grains head-1), grain yield per plant (141.37 gm plant-1), and total grain yield (10.094 tons ha-1), while the first date (D1) excelled with the highest average weight of 500 grains (16.48 gm). The results indicated that treatment T2 was superior with the highest average for the number of head grains (4835 grains head-1), grain yield per plant (132.94 gm plant-1), and the total grain yield (9.492 tons ha-1). The interaction between planting dates and stimulation parameters showed significant in the aforementioned traits, with the exception of weight 500 grain.